Triple-signaling amplification strategy based electrochemical sensor design: boosting synergistic catalysis in metal–metalloporphyrin–covalent organic frameworks for sensitive bisphenol A detection. Issue 14 (22nd June 2021) - Xie, Yao; Wang, Na; Sun, Xin; Chu, Huacong; Wang, Yang; Hu, Xiaoya
Abstract : A novel triple-signaling electrochemical sensor was constructed for bisphenol A detection using metal–metalloporphyrin–covalent organic frameworks. Abstract : A covalent organic framework (COF) is a promising type of porous material with customizable surface characteristics. Confining multiple catalytic units within a mesoporous COF can generate abundant active sites and improve the catalytic performance. In this work, a COF with both metalloporphyrin and a metal nanoparticle complex denoted as hemin/TAPB-DMTP-COF/AuNPs (TAPB: 1, 3, 5-tris(4-amino-phenyl)benzene, DMTP: 2, 5-dimethoxyterephaldehyde, AuNPs: Au nanoparticles) has been successfully fabricated through a hierarchical encapsulation method. The as-synthesized composite was then employed to construct an electrochemical sensing platform for the efficient detection of bisphenol A (BPA). Under the optimal conditions, the hemin/TAPB-DMTP-COF/AuNP sensor presented a linear range of 0.01–3 μmol L −1 and a low detection limit of 3.5 nmol L −1 . The satisfactory signal amplification is based on a triple-signaling amplification strategy due to the abundant Fe 3+ sites of Fe-porphyrin, high conductivity of AuNPs and a large specific surface area of the TAPB-DMTP-COF. The proposed method was used to measure the content of BPA in different water samples with a satisfactory recovery from 95.5 to 104.0%, suggesting the great potential of the sensor in practical applications.